Loving the Silent Tears: The Complete Book and Lyrics of the Musical - Supreme Master Ching Hai (Ocean of Love Entertainmnet, 2015)
"Loving the Silent Tears is a musical journey of the spirit that traverses the seas and continents in a timeless search for inner peace. An unprecedented musical experience, the show combined the magic of theatre, the mystical beauty of traditional dances, the soul-stirring realm of poetry - and more. Travel the globe through 16 countries, represented by a dazzling array of ancient and modern music styles, songs sung in many languages, vibrant choreography across the cultures, and of course, a diverse star-filled cast."--Publisher.